2020
DOI: 10.21203/rs.3.rs-38278/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Documentation Practice and Associated Factors among Nurses in Harari Regional State and Dire Dawa Administration Governmental Hospitals, Eastern Ethiopia

Abstract: Abstract Background: Nursing documentation is an integral and vital professional nursing practice, deals the process of recording nursing activities concerned with the care given to individual clients to assure continual effective, safe, qualified, evidence-based and individualized care. Despite of this, in Ethiopia there is a paucity of information on nursing documentation practice and its associated factors due to limited studies with methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In Ethiopia, the act of medical documentation is poorly practiced and have reported left undone [ 2 , 3 ]. The challenge for this could be due to lack of training, time, poor knowledge, and attitude of the health workers towards medical documentation [ 2 , 27 29 ]. In spite of the limited amount of studies [ 2 , 3 , 30 ] done in Public Hospitals in Ethiopia, which is limited to nursing documentation practice among nurse workers, there is limited study has been indicated among Private hospitals that take the lion share of health care delivery to the population related to medical documentation practice and its associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, the act of medical documentation is poorly practiced and have reported left undone [ 2 , 3 ]. The challenge for this could be due to lack of training, time, poor knowledge, and attitude of the health workers towards medical documentation [ 2 , 27 29 ]. In spite of the limited amount of studies [ 2 , 3 , 30 ] done in Public Hospitals in Ethiopia, which is limited to nursing documentation practice among nurse workers, there is limited study has been indicated among Private hospitals that take the lion share of health care delivery to the population related to medical documentation practice and its associated factors.…”
Section: Introductionmentioning
confidence: 99%